The application of nanotechnology in treatment of Alzheimer’s disease - Cao, Yanyan; Zhang, Run (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract The buildup of beta-amyloid plaques in the brain results in Alzheimer's disease (AD), a neurodegenerative condition. A permanent treatment for AD is not yet available. Only a slowing down of its advancement is possible with the current pharmaceutical options. Nevertheless, nanotechnology has proven to be advantageous in medical applications. It has a lot of potential for AD therapy, particularly in diagnosing the condition and providing an alternative course of treatment. In this review, we outline the developments and benefits of nanomedicines in treating AD. Prospective nanomedicines for diagnosing and surveillance therapeutic interventions for AD and other diseases of the central nervous system (CNS) may be clinically accessible, persuading the development of investigation in this field.